Análisis del patrimonio técnico en base al formulario F229 de las cooperativas de ahorro y crédito del segmento 3 del cantón Latacunga. - Caiza Guaytarilla, Joshelyn Pamela (2020)
The main problem of this research is the lack of knowledge of the technical patrimony in the Credit Unions of the segment 3, causing risk when not establishing an adequate management and control of the financial operations, besides0 it will cause the closing of the institutions and insecurity of the members at the moment of investing in them. The objective is to determine the technical equity of segment three institutions based on form F229, through bibliographic research and the revision of SEPS regulations, allowing for analysis related to solvency. The methodology used is the same quantitative approach that will allow the collection of data in the financial statements issued by the SEPS through which the calculation of the technical equity as of 30 September 2019 was made. As a result, the analysis through the interview technique of the General Manager of each cooperative, allowing the identification of knowledge level mentioned before. The results obtained by means of the calculation were able to verify that the financial institutions belonging to segment 3 maintain stable solvency indexes, exceeding the percentage required by the Superintendence of Popular and Solidarity Economy of no less than 9%, in relation to the technical equity and the risk-weighted sum of their assets and contingencies. Besides, risk levels were considered within the F229 form with 0% weighting that refers to secure recovery accounts, 20% represent amounts of money guaranteed by public sector financial institutions, 50% represent loans granted for housing and 100% represent loans or credit titles, ordinary commercial, and consumer loans.